High-intensity interval training enhances oxidative capacity and substrate availability in skeletal muscle - Hoshino, D.; Kitaoka, Y.; Hatta, H. (The Journal of Physical Fitness and Sports Medicine, 2016)
High-intensity interval training (HIIT) consists of repeated short bursts of high-intensity exercise and rest. Here we review recent work focusing on the metabolic adaptations to HIIT, especially in oxidative capacity and substrate availability in skeletal muscle. In this review, HIIT is defined as chronic training, for at least 2 weeks, involving repeated short-duration high-intensity exercise at >85% VO2 max, followed by complete rest or active rest, for any given duration of exercise and rest. First, we describe the effects of HIIT on muscle substrate oxidative metabolism, specifically in terms of mitochondria and substrate transporters. HIIT changes muscle mitochondrial content, function and dynamics. HIIT increases the protein content of transporters of glucose, lactate and fatty acids in skeletal muscle. These adaptations of mitochondria and transporter proteins improve oxidative capacity and substrate availability in skeletal muscle. Second, we introduce a potential mechanism of HIIT-induced adaptations in skeletal muscle, focusing on mitochondrial biogenesis. It is well known that a mechanism of mitochondrial biogenesis involves PGC-1alpha protein and its upstream signaling pathways including Ca2+/calmodulin-dependent protein kinase, AMP-activated protein kinase and mitogen-activated protein kinase p38. Given that mitochondrial biogenesis occurs in an exercise-intensity-dependent manner, mobilization of fast-twitch fibers and lactate accumulation are important. Finally, we discuss the future direction of HIIT research, involving systems biology approaches such as omics technologies and mathematical modeling, which may overcome current limitations and accelerate our understanding of mechanisms of HIIT-induced adaptations.